Elements of critical thinking in Malaysian teenagers’ verbal arguments / Joanne Robert - Robert, Joanne (2014)
Critical thinking is an important quality to possess for an individual as it harnesses good decision-making and problem solving skills. There have been many complaints that Malaysian students lack critical thinking skills but thus far, there is little literature to support this claim. This study was formulated as an attempt to bridge this gap. Focusing on Malaysian teenagers studying in a private school, this study attempts to identify and analyse the critical thinking elements seen in the teenager’s verbal arguments. Specifically, it attempts to ascertain the number of valid arguments present in these arguments. Then it examines if there are similarities and differences in the way Malaysian teenagers present themselves in verbal arguments. The study is qualitative in nature as data is composed of the teenager’s spoken words. The spoken words of the teenagers are then analysed using Sinnott-Armstrong’s (2009) and Stapleton’s (2001) framework. In addition, quantitative measurements are also included by attempting to present the findings in percentages. The main findings suggest that this group of Malaysian teenagers produced more invalid arguments than the number of valid arguments. The findings of this study would suggest that critical thinking is indeed lacking among teenagers during verbal arguments. The findings might be useful to educationists who are currently thinking of incorporating critical thinking and problem solving into the curriculum in schools.